Gap Analysis for Future Agricultural Education Research in Eswatini, Swaziland - Alfred F. Tsikati; Marietta P. Dlamini; Musa A. Dube (Journal of International Agricultural and Extension Education, 2019)
From the late 1970s to the early 1980s, agriculture educators began to use research as a way of verifying, creating, disseminating and applying new knowledge. However, existing literature is inconclusive on research themes covered and yet to be covered in Agricultural Education in Eswatini. Thus, this study sought to identify themes and gaps for future research in Agricultural Education in Eswatini. This was a qualitative study employing desk review in data collection. Trustworthiness of the content analysis guide was ensured through the use of experts from the Department of Agricultural Education and Extension (AEE) at the University of Eswatini (UNESWA). Data analysis was performed using frequencies and percentages. Findings of the study revealed that in Agricultural Education, gaps existed in the following thematic areas: primary themes - programme delivery methodologies and curriculum programme planning; and secondary themes- creative thinking and problem-solving; innovative instructional technologies; teaching basic and academic skills; professional staff development; educational methodologies for teaching and learning; professional preparation and competence; and needs of future agricultural workforce. The study concluded that research conducted in Agricultural Education in Eswatini is imbalanced in both primary and secondary research themes. Therefore, the Department of AEE at UNESWA must establish a research agenda to ensure that the research conducted is thematically balanced.
Keywords: Agricultural Education; primary themes; research project; research thematic areas; secondary themes; University of Eswatini